2017
DOI: 10.4206/agrosur.2017.v45n1-03
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del transporte de novillos gordos, alimentados con dos niveles de energía metabolizable, sobre su temperatura timpánica como un indicador de bienestar

Abstract: Efecto del transporte de novillos gordos, alimentados con dos niveles de energía metabolizable, sobre su temperatura timpánica como un indicador de bienestar Effect of transport of finished steers, fed with two levels of metabolizable energy, on their tympanic temperature as an indicator of well-being

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The sudden increase in activity observed between 13 : 00 and 14 : 00 h for the heat stress condition correspond to the time when the herd begins to move to the milking parlour. It has been demonstrated that movement can increase body temperature between 0.5 and 3.5°C (Mader, 2007; Arias et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The sudden increase in activity observed between 13 : 00 and 14 : 00 h for the heat stress condition correspond to the time when the herd begins to move to the milking parlour. It has been demonstrated that movement can increase body temperature between 0.5 and 3.5°C (Mader, 2007; Arias et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%